Special Protection of Human Rights of Children I: History of Children’s Rights - Hrabar, Dubravka (International Children’s Rights, 2024)
Humanity has survived thanks to children, although they have been neglected and considered somewhat less worthy than adults throughout human history. In the earliest times, as recorded by written history, they did not enjoy any rights, not even close to that of adults. Children had no rights with respect to their parents or any third person. Antiquity was quite cruel to them; however, with the rise of Christianity, they became protected (at least) from being killed (with impunity). In the Middle Ages, their use value for society was recognised, and the bourgeois revolutions of the time strengthened this recognition by increasingly exploiting children. The Industrial Revolution considered children a free labour force to be used for generating capital. However, such pressure on the survival of children gave rise to initial ideas on the need to protect children; this referred to not only the prohibition of pernicious forms of work and working hours, but also the provision of education for them. The 20th century can be termed the century of children’s rights. The first international, often non-binding, documents (declarations, proclamations, conventions) and movements emerged in that century. In conjunction with the ideas of progressive individuals, they led to an era when it would be unthinkable for children to have no rights. The entire course of establishing legal protection for children at the global level was quite slow, yet extremely important since it obliged states to treat all children equally, and these obligations broadened and deepened over time – starting from the number and type of children’s rights to the establishment of binding legal norms instead of simple principles that existed in the early beginnings. Legal analyses of the Geneva declarations and conventions are a good indicator of how the concept of children’s rights slowly but surely progressed together with the consolidation of human rights and awareness of the dignity of human beings and children as a dependent and threatened category of human beings. Keywords: history of children’s rights, Greek law, Roman law, the Enlightenment, Industrial Revolution, international documents